Biohole Effectiveness Analysis Through The Distribution Pattern of Microbes at Each Depth In Real Time On Coastal Sand - Nugroho Widiasmadi; Djoko Suwarno (Syntax Literate, 2022)
This research was conducted on coastal sand, especially for plantations, with the aim of not only restoring the health and fertility of the soil due to the use of chemical fertilizers and pesticides as well as seeing the pattern of EC distribution at each depth from the center of the biohole based on the time of observation. Through controlled microbial activity, its spread through two types of biohole, namely horizontal and vertical biohole. This research observes in real time through soil parameter sensors connected to the micro controller to changes in soil acidity, infiltration rate, conductivity electrolyte level and porosity level through soil infiltration rate. Through simulations with 2 types of biohole, it can be seen the increase in EC in each depth to the time of observation in real time. From the observations of graphs and EC standards, it can be seen that the ability of the soil to provide nutrients in the root growth zone to support the schedule and distribution patterns of planting both during vegetative growth and generative growth periods. So that we will know the proper biohole distance and spacing in order to be able to provide vegetative and generative mass nutrition based on nutrient values monitored through sensors that change the analog parameters in the micro posesor into digital information transmitted by wifi in real time. Sand coastal soil fertility simulation based on the number of microbial populations = 10 8 / cfu with Variable 1: Soil Fertility Value or Electrolyte Conductivity / EC at a depth of 26 cm from 550 uS / cm to 1238 uS / cm on day 35 and from 1238 uS / cm down to 990 uS / cm on day 40. Varibale 2: Soil Fertility Value or Electrolyte Conductivity / EC at a depth of 24 cm from 550 uS / cm up to 968 uS / cm on day 35 & from 968 uS / cm down to 842 uS / cm on day 40.